Kepemimpinan Efektif dan Motivasi Kerja dalam Penerapan Komunikasi Terapeutik Perawat - Farida Farida (Jurnal Ners, 2011)
Introduction: The objective of this study was to identify effective leadership and the work motivation with the implementation of therapeutic communication,Methods: Design used in this study was descriptive design of the correlation with the approach cross sectional study. The population of this study was all of the practising nurse in the in-patient (hospitalized) ward at the Dr. Iskak Tulungagung hospital. All datas were taken by using the method of total population of the 98 practising nurses.Results: The result of this study showed that the big proportion of the practising nurses whose ages are less than 30 years old, graduated from Diploma, status are single (unmarried), duration of work was less or same as 6 years, generally never followed a training of communication, whereas effective leadership was in the good category and the category of work motivation wasn’t better. Analysis using chi-square with alpha 0,05 showed that there was relations between the age, old the work, effective leadership and the work motivation and the implementation of therapeutic communication. The marital status and training had not relationship with the implementation of therapeutic communication.Conclusion: It is suggested that hospital should encoverage nurse manager to promote therapeutic communication among nurses.